Pengaruh Islamic Corporate Social Responsibility (ICSR) dan Profitabilitas terhadap Reputasi Perusahaan Sektor Farmasi dI ISSI Tahun 2018-2022 - Rivani Septia Ningsih; Tulus Suryanto; Dinda Fali Rifan (Jurnal Akuntansi dan Audit Syariah)
This study aims to determine the influence of Islamic Corporate Social Responsibility (ICSR) and Profitability on the reputation of Pharmaceutical sector companies listed on the Indonesian Syariah Stock Index (ISSI) in the 2018-2022 period. The method used in this study is a quantitative approach. The type of data used in this study is secondary data. The data obtained is from the financial statements of Pharmaceutical sector companies listed on the Indonesian Syariah Stock Index (ISSI) in the 2018-2022 period. The sampling technique uses Purposive Sampling with a sample of 70 companies. The data analysis used was multiple linear regression. The results of this study show that the variable Islamic corporate social responsibility affects the company's reputation. Companies that carry out ICSR disclosure properly according to the rules determined by legal entities will get a positive assessment from stakeholders, be more recognized for their existence and can improve the company's reputation. Variable Profitability affects the company's reputation. Means Profitability shows that the higher the profit generated by a company is considered a positive signal by investors related to the company's better performance so that it can increase the company's reputation. Simultaneously, the variables Islamic Corporate Social Responsibility (ICSR) and Profitability together affect the company's reputation. This means that the company is able to improve the company's reputation, with ICSR activities and high profit increases